Tourism, Smart Specialization and Sustainable Development - Romão, João (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue addresses relations between tourism activities, smart specialization strategies, and sustainable development at different territorial levels, including the local, regional, national, and international. Framed by appropriate conceptual frameworks to define the contemporary dynamics of innovation in tourism, case studies supported by advanced quantitative methods and developed in rural and urban areas of Asia, Europe, and Africa are presented and discussed. The concept of smart specialization inspires the formulation of regional innovation policies and strategies, emphasizing the importance of endogenous resources and existing territorial capabilities. By exploring the diversity and variety of each economy to develop inter-sectoral relations, this approach aims at promoting the creation of spillover effects of innovation processes supported by adequate key enabling technologies, potentially leading to the sustainable development of places, regions, and countries. As an activity that mobilizes contributions from different economic sectors, tourism may play a central role in such strategies. As described and discussed in this Special Issue, aspects related to the creative sectors of economies, information and communication technologies, traditional products and lifestyles, food production, or diverse cultural values can be mobilized to generate innovative and sustainable solutions for tourism development.